Implantoplasty-Aided Prosthetic Rehabilitation for the Management of Peri-Implantitis in Maxilla Reconstructed With Free Fibula Flap: A Clinical Report - Ajay Yerramsetti; Manju Vijayamohan; Maya Rajan Peter; Pramod Subhas (Case Reports in Dentistry)
For managing peri-implantitis, a variety of treatment modalities involving both surgical and nonsurgical methods including implantoplasty have been proposed. Implants that are placed in a free fibula flap are more prone to peri-implantitis due to the absence of firm, keratinized mucosa. Prosthetic design that offers adequate hygiene access should be designed whenever possible; otherwise, it may lead to the accumulation of plaque or biofilm that may lead to peri-implant diseases. Implantoplasty, which is performed in advanced peri-implantitis cases that cause exposure of implant threads, has been proposed as a reliable approach to preventing progressive peri-implant bone loss by modifying the exposed implant surface. This clinical report details the management of severe peri-implant bone loss in a maxilla reconstructed with a free fibula flap by combining soft tissue management, implantoplasty, and prosthetic rehabilitation.